Strategies for managing patients with borderline personality disorder in palliative care - Cerra, Mercedes (2026)
The care of patients with Borderline Personality Disorder (BPD) in palliative care settings presents specific challenges for healthcare teams. These difficulties are associated with affective dysregulation, emotional instability, and rigid coping styles which, in the context of suffering related to a life-threatening illness, may hinder the therapeutic relationship, symptom management, communication, and shared decision-making. Since relief of suffering and treatment adherence largely depend on the establishment of a trusting relationship between the patient and the healthcare team, it is essential to develop strategies that support the continuity of care. Additionally, it is recognized that these cases can generate distress and emotional exhaustion among professionals, making it crucial to provide resources that also support the well-being of the team. This article aims to identify conceptual and practical tools that contribute to the comprehensive care of patients with BPD in palliative care settings, based on a narrative review of the literature and experience within interdisciplinary teams. Strategies addressing the needs of both patients and their families, as well as those promoting healthcare team well-being, will be analyzed, with the purpose of strengthening the therapeutic relationship and preventing professional burnout.